Status of thyroid autoantibodies among Nigerian vitiligo patients - Amadi, Collins; Odum, Ehimen P. (International Journal of Scientific Reports, 2018)
Background: The prevalence of thyroid autoantibodies among vitiligo patients is higher than the general population. This study was therefore aimed to evaluate the status of thyroid autoantibodies in Nigerian patients with vitiligo. Methods: A retrospective study of thyroid autoantibody test parameters of vitiligo patients who visited the Department of Chemical Pathology and Metabolic Medicine of the University of Port Harcourt Teaching Hospital between 1st January 2012 and 31st December 2016 was undertaken to evaluate the status of thyroid autoantibody. Data collected irrespective of vitiligo variant were age, sex, serum thyroid stimulating hormone (TSH), thyroid peroxidase antibody (anti-TPO) titers and thyroglobulin antibody (anti-Tg) titers. The analysis was done using Shapiro-Wilk, descriptive statistics, chi-square, and Fisher’s exact, two-sample t-test. The level of p<0.05 was considered significant. Results: There were a total of 102 subjects with 40 (39.2%) males and 62 (60.8%) females. Subjects’ age ranged from 4–61 with a median value of 23 years. The mean serum TSH, anti-TPO and anti-Tg were 2.6 IU/ml, 64.6 IU/ml, and 55.2 IU/ml respectively. Positive thyroid autoantibodies titers was documented in 35 (34.3%; <0.001) subjects. Anti-TPO and anti-Tg positive titers were detected in 34 (33.3%) and 19 (18.6%) subjects respectively, while autoimmune thyroid disease was observed in 20 (19.6%) of the vitiligo subjects. Conclusions: Thyroid autoantibodies are more prevalent among vitiligo patients than the general population. Regular screening for these thyroid autoantibodies should be made compulsory in the management of patients with vitiligo.